Production of Phytotoxic Metabolite Using Biphasic Fermentation System from Strain C1136 of Lasiodiplodia pseudotheobromae, a Potential Bioherbicidal Agent - Charles Oluwaseun ADETUNJI; Julius Kola OLOKE; Gandham PRASAD; Moses ABALAKA; Emenike Onyebum IROKANULO (Notulae Scientia Biologicae, 2017)
Formulation of effective and environmental friendly bioherbicides depends on the type of fermentation medium used for the production of phytotoxic metabolites. The effect of biomass, colony forming unit and the phytotoxic metabolite produced from the biphasic fermentation was carried out, while the phytotoxic metabolite was tested in vivo and in-vitro on Echinochola crus-galli and dicotyledonous Chromolaena odorata. The mutant strain of Lasiodiplodia pseudotheobromae C1136 (Lp90) produced the highest amount of conidia and the largest necrotic area on the two tested weeds when compared to its wild strain in the different biphasic media combinations. The study revealed that the biphasic system containing PDB + rice produced the highest bioherbicidal activities. Therefore, the phytotoxic metabolites from strain C1136 are suggested for large scale production of bioherbicides for the management of weeds in conventional farming to improve yield and enhance food security.